IS IT TOO DIFFICULT FOR STUDENTS TO LEARN ENGLISH? A CASE STUDY OF STUDENTS' HABITS IN USING EXTENSIVE LISTENING/VIEWING - Ardianto, Puthut; Fitrah Nurcahya, Andika (Universitas Sarjanawiyata Tamansiswa, 2023)
Developing habits related to studying the English language will help you improve your English-speaking abilities. This study aims to identify the behaviors that, in the eyes of the students in the English Language Education Department, improve English-speaking abilities as well as how those habits helped to improve those abilities. The case study research design was used in this study, which used a qualitative methodology. A student in the English Language Education Department of a private institution in Yogyakarta served as the study's participant. Interviews and reflections served as the research instruments for this study. The results showed that his habits of listening to English songs, watching English movies, reading the news, and engaging in self-talk had a substantial impact on the development of his speaking abilities. While the activities that contributed to the improvement of English language skills were slowing down the music and understanding the lyrics from the activity of listening to English music, reading the movie subtitles from the activity of watching English movies, selecting favorite topic news from the activity of reading news, and doing repetition from the activity of self-talk. Keywords: extensive listening, speaking, habits